2011
DOI: 10.1136/pgmj.2011.118885
|View full text |Cite
|
Sign up to set email alerts
|

General practice and social service partnership for better clinical outcomes, patient self efficacy and lifestyle behaviours of diabetic care: randomised control trial of a chronic care model

Abstract: Current Controlled Trials ISRCTN78882965.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 33 publications
1
40
0
Order By: Relevance
“…This has been previously shown in other populations, including patients with other chronic diseases, as well [11,18,43]. Two recently published randomized controlled trials by Shi et al in China, and Lee et al in Hong Kong, testing interventions to improve self-efficacy for diabetes have also reported improvement in glycemic control with increased self-efficacy [22,38].…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…This has been previously shown in other populations, including patients with other chronic diseases, as well [11,18,43]. Two recently published randomized controlled trials by Shi et al in China, and Lee et al in Hong Kong, testing interventions to improve self-efficacy for diabetes have also reported improvement in glycemic control with increased self-efficacy [22,38].…”
Section: Discussionmentioning
confidence: 64%
“…The calculated BMI was categorised based on the WHO expert consultation recommendations, into below normal (\18), normal (18)(19)(20)(21)(22).99), high normal (23-24.99), overweight (25-29.99) and obese (30 and above) [2].…”
Section: Body Mass Index (Bmi)mentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristic of the included studies are presented in Table 1 . Only one study reported blinding of both patients and data collectors [ 13 ] and one other study [ 14 ] reported blinding of patients only.…”
Section: Reviewmentioning
confidence: 99%
“…Self-management support is a broad concept stretching well beyond the medical domain, to a range of community resources (Fig 1, Supplementary data file Table S1); and broader partnerships providing input may for example improve care in diabetes [46]. Such multi-faceted data sources may lend themselves well to ontological exploration.…”
Section: Self-management Supportmentioning
confidence: 99%